Pakistan : a personal history - Khan, Imran, 1952- (London : Bantam, 2011)
Recounting Pakistan's history through the prism of the author's own memories, this title starts from its foundation, ripped out of the dying British Raj. It guides us through and comments on subsequent historical developments which shook the Muslim world - from the wars with India in 1965 and 1971, to the controversial war in Afghanistan.
Recounting Pakistan's history through the prism of the author's own memories, this title starts from its foundation, ripped out of the dying British Raj. It guides us through and comments on subsequent historical developments which shook the Muslim world - from the wars with India in 1965 and 1971, to the controversial war in Afghanistan.
Includes index.
Keywords: Khan, Imran, -- 1952- -- Biography; Pakistan -- History